THE ROLE OF ACEHNESE ULAMA THOUGHT IN ISLAMIC FAMILY LAW REFORM IN THE GLOBALIZATION ERA - Salim Mahmudi, Muhammad; Hamdi Muhammad Abdul Ghaffar , Walid; Hidayat, Taufiq; Amiruddin , Amiruddin; Jani, Rafsan (Academic Journal Research, 2025)
Objective: This study aims to explore the thoughts of Acehnese scholars on Islamic family law and their role as catalysts for inclusive and adaptive legal reform. It investigates how these perspectives address the challenges of globalization while contributing to social justice and family welfare in Aceh. Methods: The research employs a library research approach, gathering data from written sources, including books, scientific journal articles, research reports, and legal documents relevant to the subject. The study critically analyzes these sources to understand the influence and interpretation of Islamic family law by Acehnese scholars. Results: The findings reveal three key points: (1) Acehnese scholars direct their thoughts toward adapting sharia to contemporary challenges, focusing on issues such as dowry, divorce, and women's rights. (2) The main challenges in interpreting Islamic family law include reconciling traditional and modern values and mitigating the influence of globalization, which often undermines sharia understanding. (3) The scholars' perspectives positively influence the renewal of family law, evident in local policies such as Aceh Qanun and the development of more inclusive and progressive regulations. Novelty: This research highlights the innovative role of Acehnese scholars in shaping Islamic family law to address globalization's challenges. It emphasizes their contributions to fostering inclusive legal frameworks and advancing family law reforms in Aceh, which serve as a model for balancing tradition and modernity within an Islamic context.